Wardlaw's perspectives in nutrition : a functional approach - Byrd-Bredbenner, Carol (McGraw Hill, 2014)
Helps students benefit from a carefully crafted text that brings them scientific thinking and research blended with dynamic activities that can allow them to apply their knowledge to their own lives and future careers. This book brings together the digital technology in a single cohesive learning experience